Effects of residential ventilation and filtration interventions on adult asthma outcomes - Insung Kang; Anna McCreery; Parham Azimi; Mingyu Wang; Amanda Gramigna; Griselda Baca; Timothy Crowder; Rachel Scheu; Anne Evens; Brent Stephens (Building and Environment, 2025)

Projecting climate change impacts from physics to fisheries: A view from three California Current fisheries - James A. Smith; Mercedes Pozo Buil; Barbara Muhling; Desiree Tommasi; Stephanie Brodie; Timothy H. Frawley; Jerome Fiechter; Stefan Koenigstein; Amber Himes-Cornell; Michael A. Alexander; Steven J. Bograd; Nathalí Cordero Quirós; et al. (Progress in Oceanography, 2023)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Social relationship dynamics mediate climate impacts on income inequality: evidence from the Mexican Humboldt squid fishery - Laura G. Elsler; Timothy Haight Frawley; Gregory L. Britten; Larry B. Crowder; Timothy C. DuBois; Sonja Radosavljevic; William F. Gilly; Anne-Sophie Crépin; Maja Schlüter (Regional Environmental Change, 2021)
Small-scale fisheries are critically important for livelihoods around the world, particularly in tropical regions. However, climate variability and anthropogenic climate change may seriously impact small-scale fisheries by altering the abundance and distribution of target species. Social relationships between fishery users, such as fish traders, can determine how each individual responds and is affected by changes in fisheries. These informal cooperative and competitive relationships provide access, support, and incentives for fishing and affect the distribution of benefits. Yet, individuals’ actions and impacts on individuals are often the primary focus of the economic analyses informing small-scale fisheries’ formal management. This focus dismisses relevant social relationships. We argue that this leads to a disconnect between reality and its model representation used in formal management, which may reduce formal fisheries management’s efficiency and efficacy and potentially trigger adverse consequences. Here, we examine this argument by comparing the predictions of a simple bioeconomic fishery model with those of a social-ecological model that incorporates the dynamics of cooperative relationships between fish traders. We illustrate model outcomes using an empirical case study in the Mexican Humboldt squid fishery. We find that (1) the social-ecological model with relationship dynamics substantially improves accuracy in predicting observed fishery variables to the simple bioeconomic model. (2) Income inequality outcomes are associated with changes in cooperative trade relationships. When environmental temperature is included in the model as a driver of species production dynamics, we find that climate-driven temperature variability drives a decline in catch that, in turn, reduce fishers’ income. We observe an offset of this loss in income by including cooperative relationships between fish traders (oligopoly) in the model. These relationships break down following species distribution changes and result in an increase in prices fishers receive. Finally, (3) our social-ecological model simulations show that the current fishery development program, which seeks to increase fishers’ income through an increase in domestic market demand, is supported by predictions from the simple bioeconomic model, may increase income inequality between fishers and traders. Our findings highlight the real and urgent need to re-think fisheries management models in the context of small-scale fisheries and climate change worldwide to encompass social relationship dynamics.

Decision Support for Potato Growers using a Pest Monitoring Network - Carrie H. Wohleb; Timothy D. Waters; David W. Crowder (American Journal of Potato Research, 2021)

How adaptive capacity shapes the Adapt, React, Cope response to climate impacts: insights from small-scale fisheries - Kristen M. Green; Jennifer C. Selgrath; Timothy H. Frawley; William K. Oestreich; Elizabeth J. Mansfield; Jose Urteaga; Shannon S. Swanson; Francisca N. Santana; Stephanie J. Green; Josheena Naggea; Larry B. Crowder (Climatic Change, 2021)

Heterogeneous Perceptions of Social-Ecological Change Among Small-Scale Fishermen in the Central Gulf of California: Implications for Adaptive Response - Timothy H. Frawley; Larry B. Crowder; Kenneth Broad (Frontiers in Marine Science, 2019)

Reconstructing overfishing: Moving beyond Malthus for effective and equitable solutions - Elena M Finkbeiner; Nathan J Bennett; Timothy H Frawley; Julia G Mason; Dana K Briscoe; Cassandra M Brooks; Crystal A Ng; Rosana Ourens; Katherine Seto; Shannon Switzer Swanson; Jose Urteaga; Larry B Crowder (Fish and Fisheries, 2017)
Inaccurate or incomplete diagnosis of the root causes of overfishing can lead to misguided and ineffective fisheries policies and programmes. The “Malthusian overfishing narrative” suggests that overfishing is driven by too many fishers chasing too few fish and that fishing effort grows proportionately to human population growth, requiring policy interventions that reduce fisher access, the number of fishers, or the human population. By neglecting other drivers of overfishing that may be more directly related to fishing pressure and provide more tangible policy levers for achieving fisheries sustainability, Malthusian overfishing relegates blame to regions of the world with high population growth rates, while consumers, corporations and political systems responsible for these other mediating drivers remain unexamined. While social–ecological systems literature has provided alternatives to the Malthusian paradigm, its focus on institutions and organized social units often fails to address fundamental issues of power and politics that have inhibited the design and implementation of effective fisheries policy. Here, we apply a political ecology lens to unpack Malthusian overfishing and, relying upon insights derived from the social sciences, reconstruct the narrative incorporating four exemplar mediating drivers: technology and innovation, resource demand and distribution, marginalization and equity, and governance and management. We argue that a more nuanced understanding of such factors will lead to effective and equitable fisheries policies and programmes, by identifying a suite of policy levers designed to address the root causes of overfishing in diverse contexts.

Formulation of a dry powder influenza vaccine for nasal delivery - Robert J. Garmise; Kevin Mar; Timothy M. Crowder; C. Robin Hwang; Matthew Ferriter; Juan Huang; John A. Mikszta; Vincent J. Sullivan; Anthony J. Hickey (AAPS PharmSciTech, 2006)

Fundamental Effects of Particle Morphology on Lung Delivery: Predictions of Stokes' Law and the Particular Relevance to Dry Powder Inhaler Formulation and Development - Timothy M. Crowder; Jacky A. Rosati; Jeffry D. Schroeter; Anthony J. Hickey; Ted B. Martonen (Pharmaceutical Research, 2002)

The problem of a solvent exposable disulfide when preparing Co(II)-substituted metallo-β-lactamase L1 from Stenotrophomonas maltophilia - Michael W. Crowder; Ke-Wu Yang; Anne L. Carenbauer; Gopal Periyannan; Mary E. Seifert; Nathan E. Rude; Timothy R. Walsh (JBIC Journal of Biological Inorganic Chemistry, 2001)